STRATEGI KOMUNIKASI MASYARAKAT URBAN DALAM ADAPTASI DI KOTA PONTIANAK - Martina NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Language as a means of communication in community has an important role in life,both urban and local communities. Theories applied in this paper include interculturalcommunication (Liliweri, 2016), language studies (Yule, 2014), sociolinguistics(Sumarsono, 2013), and other related theories. This paper aims to describe urbancommunity communication strategies in adapting in Pontianak City. The methodapplied is descriptive method with qualitative approach. The result of the analysisshows that communication strategy used by urban community to adapt in Pontianakcity through culture, language, and society. The form of adaptation of urban societythrough culture in Pontianak City by showing the characteristic of its culture so asgiving space and its own value for society in that city. In practice, these culturalactivities use ethnic language (Dayak language, Chinese language, and Malay dialectof Pontianak) and Indonesian language.